Combating Repeated Lies: The Impact of Fact-Checking on Persistent Falsehoods by Politicians - Irene Larraz; Ramón Salaverría; Javier Serrano-Puche (Media and Communication)
The rise of repeated false claims within political discourse is undermining fact-checking efforts. By reiterating similar statements that perpetuate previous falsehoods, political actors shift from misinformation to deliberate disinformation and even propagandistic tactics. Through an analysis of 1,204 political fact-checks conducted by the Spanish fact-checking organization Newtral, this study quantifies and characterizes the prevalence of repeated false claims in political discourse, revealing that a substantial 24.8% of false statements are repeated, with each being repeated an average of four times. By delving into the nature and types of claims most susceptible to recurrence, the study identifies five primary patterns employed by political actors: nuanced variations, data manipulation, multilateral attacks, discourse qualification, and cumulative repetition. These tactics blur the lines between deception and self-correction. The annotated database of these repeated false statements can serve as a valuable resource for exploratory qualitative analysis as well as claim-matching research in automated fact-checking.